Orexin receptor antagonist-induced sleep does not impair the ability to wake in response to emotionally salient acoustic stimuli in dogs - Tannenbaum, Pamela L.; Stevens, Joanne; Binns, Jacquelyn; Savitz, Alan T.; Garson, Susan L.; Fox, Steven V.; Coleman, Paul; Kuduk, Scott D.; Gotter, Anthony L.; Marino, Michael; Tye, Spencer J.; Uslaner, Jason M.; et al. (Frontiers in Behavioral Neuroscience, 2014)
The ability to awaken from sleep in response to important stimuli is a critical feature of normal sleep, as is maintaining sleep continuity in the presence of irrelevant background noise. Dual orexin receptor antagonists (DORAs) effectively promote sleep across species by targeting the evolutionarily conserved wake-promoting orexin signaling pathway. This study in dogs investigated whether DORA-induced sleep preserved the ability to awaken appropriately to salient acoustic stimuli but remain asleep when exposed to irrelevant stimuli. Sleep and wake in response to DORAs, vehicle, GABA-A receptor modulators (diazepam, eszopiclone and zolpidem) and antihistamine (diphenhydramine) administration were evaluated in telemetry-implanted adult dogs with continuous electrocorticogram, electromyogram, electrooculogram, and activity recordings. DORAs induced sleep, but GABA-A modulators and antihistamine induced paradoxical hyperarousal. Thus, salience gating studies were conducted during DORA-22 (0.3, 1, and 5 mg/kg; day and night) and vehicle nighttime sleep. The acoustic stimuli were either classically conditioned using food reward and positive attention (salient stimulus) or presented randomly (neutral stimulus). Once conditioned, the tones were presented at sleep times corresponding to maximal DORA-22 exposure. In response to the salient stimuli, dogs woke completely from vehicle and orexin-antagonized sleep across all sleep stages but rarely awoke to neutral stimuli. Notably, acute pharmacological antagonism of orexin receptors paired with emotionally salient anticipation produced wake, not cataplexy, in a species where genetic (chronic) loss of orexin receptor signaling leads to narcolepsy/cataplexy. DORA-induced sleep in this species thereby retains the desired capacity to awaken to emotionally salient acoustic stimuli while preserving uninterrupted sleep in response to irrelevant stimuli.